A double blind randomized clinical trial comparing lingualized and fully bilateral balanced posterior occlusion for conventional complete dentures. Issue 2 (April 2017) - Kawai, Yasuhiko; Ikeguchi, Nobuyuki; Suzuki, Asako; Kuwashima, Azusa; Sakamoto, Ryuji; Matsumaru, Yuichi; Kimoto, Suguru; Iijima, Morio; Feine, Jocelyne Sylvia
Abstract: Purpose: A lingualized occlusion (LO) for complete dentures reduces lateral inferences and occlusal force contacts and direction; thus, LO is theorized to be more suitable for patients with compromised ridges than fully bilateral balanced articulation (FBBA). However, no studies have yet provided evidence to support LO in edentate patients with compromised alveolar ridges. The purpose of this study was to compare LO and FBBA in edentulous individuals with compromised ridges. Methods: Sixty edentulous individuals were randomly allocated into groups and received dentures with either LO or FBBA. Following delivery, several denture-related satisfaction variables were measured using 100 mm visual analogue scales; oral health-related quality of life (OHRQoL) was also assessed using the Oral Health Impact Profile (OHIP). Sub-group analyses of the effect of moderate and severe mandibular bone loss were also carried out. Results: No significant differences were detected between LO and FBBA with the primary outcome. At 6 months, participants with severely atrophied mandibles and FBBA rated their satisfaction with retention of mandibular dentures significantly lower than those with LO (median LO: 86, FBBA: 58.5, p = 0.03). They also had significantly lower OHRQoL for the domain of Pain (median LO: 4, FBBA: 5, p = 0.02). General satisfaction and total OHIP scores significantly improved between baseline and 6 months only for the LO subjects with severely atrophied mandibles (satisfaction: p = 0.003, OHIP total score: p = 0.0007). Conclusions: The results indicate that the LO occlusal scheme with hard resin artificial teeth is more efficient for patients with severely resorbed mandibular ridges.